Growth, carbon assimilation and biochemical changes of polygonum minus huds as affected by nitrogen fertilization - Ibrahim, Mohd Hafiz; Muah, Nurul Najaa; Mohd Zain, Nurul Amalina (Sciencedomain International, 2018)
Aims: To study the effect of different nitrogen fertilizer rates on growth, carbon assimilation and biochemical changes of Polygonum minus. Study Design: Polygonum minus were treated with different nitrogen fertilizer (0 kg N ha-1, 50 kg N ha-1, 100 kg N ha-1 and 150 kg N ha-1) using Urea (46%N) as a source of nitrogen. This experiment was arranged in Randomized Complete Block Design (RCBD) with three replications. Place and Duration of Study: The experiment was conducted at Taman Pertanian Universiti(TPU), Universiti Putra Malaysia between April 2017 to July 2017. Methodology: The growth parameters measured includes the leaf number, plant height, diameter of the stem, and the leaf area. The carbon assimilation parameters were measured using LICOR 6400XT Portable Photosynthesis System. Total phenolic and flavonoids contents from the leaves extracts of Polygonum minus were measured using Folin-Ciocalteu reagents.Results: The best rates of nitrogen in enhancing the best growth and quality of Polygonum minus was observed at 150 kg N ha-1 in most parameters of growth and carbon assimilation. At the final harvest, the parameters such as number of leaves, plant height, stem diameters, total chlorophyll contents, leaves area, total dry weight, net assimilation rate (NAR), water use efficiency (WUE), net photosynthesis rate (A) stomatal conductance (gs), and maximal efficiency of photosystem II (fv/fm)were highest at 150 kg N ha-1 treatments. In the terms of biochemical changes, the parameter such as total phenolics contents and total flavonoids gain the highest production of total phenolics and flavonoids at 50 kg N ha-1. Conclusion: This study indicated growth and carbon assimilation parameters were upregulated under higher nitrogen fertilization and production of secondary metabolites was decreased with high rates of nitrogen. The recommended nitrogen fertilization for P. minus was at 50 kg N Ha-1,where it obtained the highest harvest index.